Synthesis and Processing of Near Infrared—Activated Vitrimer Nanocomposite Films Modified with β-Hydroxyester-Functionalized Multi-Walled Carbon Nanotubes - Byrne Prudente, Tomas Eduardo (2023)
Films of a vitrimer based on the reaction between diglycidylether of bisphenol A and glutaric acid in the presence of 1-methylimidazole were processed using a solvent-based technique. The curing schedule was divided into two steps: first, a soluble linear polymer was formed through the reaction of the diacid and the diepoxide, and then the crosslinking was induced at a higher temperature via transesterification reactions. This epoxy–acid vitrimer was modified with multi-walled carbon nanotubes (MWCNTs) functionalized with β-hydroxyesters, produced by a robust and straightforward strategy based on a two-phase reaction between oxidized MWCNTs and phenylglycidylether. Nanocomposite vitrimer films were obtained by drop casting a dispersion of the functionalized MWCNTs in the linear polymer/cyclohexanone solution, followed by a thermal treatment. A high degree of dispersion of the carbon nanostructures was attained thanks to the β-hydroxyester functionalization when compared with oxidized MWCNTs. Nanocomposite films showed a significant photothermal effect (reaching 200 ◦C or above in 30 s) upon NIR light irradiation (850 nm) from a single LED (500 mW/cm2 ). The released heat was used to activate the shape memory effect and weld and heal the vitrimer matrix, proving the success of this easy strategy for the generation of remotely activated carbon-based vitrimer nanocomposites.